Republic of San Marino : 2010 Article IV Consultation - Staff Report; Supplement to the Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for San Marino. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the economic development and growth of San Marino are discussed. For liquidity management, the Central Bank of San Marino was commended. Different measures have been taken to enhance the operational autonomy of the Central Bank of San Marino (CBSM), buttress supervisory functions, and strengthen Antimoney Laundering and Combating the Financing of Terrorism (AML/CFT). The goals to reduce the fiscal deficit are encouraged, but counseled that the credibility of fiscal plans would be enhanced by a better-articulated strategy. Cuts in public sector employment through attrition and reforms could be the key elements of this strategy.